Do Individual Investors Ignore Transaction Costs? - Anginer, Deniz (World Bank, Washington, DC, 2017)
Using close to 800,000 (2,000,000) transactions by 66,000 (303,000) households in the United States (in Finland), this paper shows that individual investors with longer holding periods choose to hold less liquid stocks in their portfolios, consistent with Amihud and Mendelson's (1986) theory of liquidity clienteles. The relationship between holding periods and transaction costs is stronger among more financially sophisticated households. Households whose holding periods are positively related to transaction costs also earn higher gross returns on their investments before accounting for transaction costs, suggesting that attention to non-salient transaction costs is an indication of investing ability. The main findings are confirmed by analyzing changes in investors' holding periods around exogenous shocks to stock liquidity.